2003
DOI: 10.1034/j.1399-302x.2003.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal immunization of humans with Streptococcus mutans antigens

Abstract: To evaluate the effectiveness of a low dose of soluble or liposomal (L) glucosyltransferase-enriched preparation (E-GTF) in inducing mucosal immune responses after intranasal immunization, 12 adults were immunized on days 0 and 7 by the IN route with 62.5 microg of soluble E-GTF or L-E-GTF. An increase in the mean salivary IgA anti-E-GTF response (P < 0.03) was seen in the L-E-GTF but not the soluble E-GTF group. A significant increase (P < 0.05) in the mean specific IgA antibody activity was also seen in nasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
0
12
0
2
Order By: Relevance
“…At least three S. mutans glucan-binding proteins GbpA, GbpB and GbpC were identified to date [37]. Only GbpB, which is 431 residues long and has a calculated molecular weight of 41.3 kD, has been shown to induce protective immune responses to experimental dental caries.…”
Section: Glucan-binding Proteins (Gbp)mentioning
confidence: 99%
See 1 more Smart Citation
“…At least three S. mutans glucan-binding proteins GbpA, GbpB and GbpC were identified to date [37]. Only GbpB, which is 431 residues long and has a calculated molecular weight of 41.3 kD, has been shown to induce protective immune responses to experimental dental caries.…”
Section: Glucan-binding Proteins (Gbp)mentioning
confidence: 99%
“…For example, oral administration of capsules containing glucosyltransferases (GTF) from S. sobrinus combined with aluminum phosphate could result in an increase in sIgA antibody response in 14 human subjects, which showed interference with proportions of indigenous mutans streptococci/total streptococcal flora, or total cultivable flora in the oral cavity [44,45]. Intranasal immunization of humans with S. mutans antigens could also induce an IgA response in secretions [37]. However, no vaccines have been brought to market though we are now in the fifth decade of vaccine approaches intended to prevent or arrest dental caries.…”
mentioning
confidence: 99%
“…The nose, like the mouth, is a practical site for vaccine administration, and NALT stimulation efficiently induces antigen-specific immune responses in both mucosal and systemic compartments (15,28). In the past decade, several clinical studies have confirmed that local immunity and systemic immunity are generated after nasal immunization of humans against diphtheria and tetanus (2), influenza (21), and infection with Streptococcus mutans (32). A large number of studies performed with mice, pigs, and monkeys have also confirmed the effectiveness of nasal immunization with a variety of vaccines (15).…”
mentioning
confidence: 99%
“…Streptococcus mutans tem sido a mais estudada pela sua mais freqüente relação com o desenvolvimento de cárie, como demonstrado em estudos de detecção destes microrganismos por métodos de cultivo laboratorial (LI et al, 2003) e por métodos moleculares (BECKER et al, 2002).…”
Section: Cárie Radicularunclassified